Monitoring Development Board based on InfluxDB and Grafana - Noprianto Noprianto; Vivi Nur Wijayaningrum; Rokhimatul Wakhidah (Telematika, 2023)
Purpose: Designing a sensor data monitoring system using a time series database and monitoring platform on a Development Board device.Design/methodology/approach: It begins with a requirement analysis, such as the preparation of the required software and hardware, followed by the creation of the system architecture that will be adopted. Then the development process from a predetermined design to the testing process to ensure the dashboard page can display data according to a predetermined scenario.Findings/result: From the research that has been done, produces a design of sensor data that is sent using the MQTT protocol via Node-RED, then stored in a time series database (InfluxDB) and displayed on the Grafana dashboard display.Originality/value/state of the art: Sensor data monitoring dashboard on Development Board devices